Humans in the focus of new challenges - Danilov, Alexander N.; Burak, Petr M.; Bondar, Yuri P.; Vodopianov, Pavel A.; Volotovski, Igor D.; Zelenkov, Anatoly I.; Kurbatski, Alexander N.; Mojeiko, Marina A.; Myasnikovich, Mikhail V.; Rakhmanov, Sergei K.; Shchetkina, Marianna A. (Journal of the Belarusian State University. Sociology, 2026)
The state of global society and global ecosystem in the context of growing systemic threats is analysed. The round table participants noted the absence of a global development strategy and a clear vision of ways to achieve a secure future. Against the backdrop of the evolution of humanity as a biosocial system, the strengthening role of the social component and insufficient attention to the humanistic factors of development are emphasised. Ignorance of the laws of nature, which leads to the destruction of the human habitat in its natural state, is pointed out. International cooperation of constructive expert and analytical communities, as well as systemic intellectualisation and humanisation of the scientific and educational sphere are proposed as possible tools for solving these problems. Particular attention is paid to the need to return to the fundamental mission of education, including university education – the formation of a conscious person, and not a qualified consumer.
Keywords: humans; new challenges and risks; artificial intelligence; sociodynamics; safe future; global society; global ecosystem; biosocial system; humanistic factors of development; international cooperation; humanisation of education; university mission; personality development